MEASUREMENT OF THE BEST METHOD BETWEEN CERTAINTY FACTOR AND BAYES THEOREM METHODS IN EXPERT SYSTEM BY USING SPSS AND ODM APPLICATIONS - Dwiparaswati, Windy (Universitas Gunadarma, 2017)
The science that study how to make a computer can act and have the intelligence of a human being is called artificial intelligence. One field of artificial intelligence is expert systems. Expert system must be able to work in uncertainty. Many researchers use methods in making expert system in a particular domain. In detecting a disease in an expert system, the results of data accuracy is a critical component for the achievement of the expected solution. Two studies explain the differences in the results of the accuracy of the Certainty Factor and Bayes method, although using the same domain that chronic kidney disease. This study aims to use the method of Certainty Factor (CF) and Bayes Theorem in representing the calculation results of ASD in children under 5 years old, compare the final value result of the Certainty Factor and Bayes Theorem Method, determine the best method between certainty factor and Bayes Theorem that has the best accuracy in detecting the possibility of children affected by autism spectrum disorders, with the application of SPSS and ODM. The final accuracy show 66.67% states that the final accuracy value use certainty Factor and Bayes method is as good on SPSS application, and 33.33% states that Certainty Factor which is the best method on ODM application.